If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 6 = 48 Reorder the terms: 6 + b = 48 Solving 6 + b = 48 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + b = 48 + -6 Combine like terms: 6 + -6 = 0 0 + b = 48 + -6 b = 48 + -6 Combine like terms: 48 + -6 = 42 b = 42 Simplifying b = 42
| -5.12+(-4.31)=-(m+4.31) | | N/4=15/10 | | (6+5)(b+3)= | | (2a+3b)(a-b)= | | 6.4=-4x | | -(x+4.16)=-3-4.16 | | P-15=3(2-P)+P | | X+3y=66 | | 2(14a+a)-6=24 | | 32+(z+91)=91+32-51 | | 30x-7=10 | | 3x-6=10x+15 | | 8(3/8)=20t(-1/8) | | (a+6)(a+4)= | | 3/7•3 | | 12+(13+y)=25+7 | | 450000-22000x=12000x+(-155000) | | 3x-7=x+14 | | X^2+8x+8=2x | | 3x-7=x+18 | | 450000-22000x=12000x+(155000) | | ydx+(x^2-4x)dy=0 | | (-3ln+lnx)=0 | | x^3-16x-16=0 | | X^2=-12x+64 | | 7+3(x-7)=1-5(x-6) | | -7k=-6k^2 | | -60=x^2-16x | | 2j^2-4j-30=0 | | (4x+3)+57=180 | | (-2x-50)(x+17)=0 | | 3X+42=84 |